Along the Banks of the River Vishwamitri (A Floristic Study) - Cravan, A. R.; Sabnis, S. D. (Indian Forester, 1960)
1. There is a definite lack of data on the ecology of the vegetation in and around running water. The authors, in the present paper, have made a study of the floristic composition and seasonal changes in the vegetation in keeping with a change in the water level of the river. 2. 151 plants belonging to 45 families-38 dicotyledonous and 7 monocotyledonous-have been recorded. More attention has been paid to the ephemeral flora occupying the lowermost storey. 3. Seasonal changes in the vegetation have been discussed. The vegetation of upper and middle storeys is left undisturbed as it is beyond the reach of water except in the years of excessive rainfall. This vegetation is characterised by the presence of trees, shrubs or woody perennials. The vegetation of the lowermost storey is ephemeral in the sense that it is totally destroyed by the rising water level during the monsoon. It is only during the hot months that the various tiers of vegetation can be studied simultaneously. The ephemeral flora is dominated by the presence of herbaceous annuals. The water surface during the dry months shows floating hydrophytes such as Lemna, Ipomoea and submerged hydrophytes like Ceratophyllum, Vallisneria, Hydrilla and Chara. 4. Seasonal changes in the vegetation due to changes in the water level in the tributaries follow a somewhat similar pattern. The permanent vegetation remains the same but the ephemeral vegetation is akin to the 'Recession zone' vegetation of the ponds and puddles. 5. Factors like widening of the river, construction of embankments, overgrazing and cutting of grass have affected the growth of vegetation along the banks of the river.